Transparency vs. Corruption: The Case of Republic of Macedonia - S. Dzamtovska-Zdravkovska; J. Denkova; A. Majhosev (University of Sofia, 2014)
Today citizens are increasingly becoming an equal entity with state institutions which have responsibility to ensure protection of their rights, accountability, openness and transparency in its operations - as the basic principles upon which rests the principle of good governance. The traditional model of not transparent administration today disappears step by step. Adoption of a law of free access to public information in many countries in the world which seek to enhance democracy in their societies today is a process that can not stop. Nowadays, countries that do not have such a law can not claim that they have full democracy. One of the reasons for passing this law is reducing corruption. Corruption is based on secrecy. Citizens and institutions become corrupted when the public has no insight into their work. If the work of public institutions is transparent and offered for public inspection, then the chance for them to be corrupt is smaller. This paper analyzes the Law of free access to public information in the Republic of Macedonia and its application; the situation in Macedonia after the adoption of the law; concluding that despite some inconsistencies, the law has contributed to increasing transparency and reducing corruption.